Analogue modulator for psychoacoustical pulse measurements - JAROSZEWSKI, Antoni; RAKOWSKI, Andrzej (Archives of Acoustics, 1976)
A general description and some diagrams of the three channel analogue modulator are given. Some more important details of the construction are discussed.